2009
DOI: 10.1002/rra.1241
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and inter‐annual variability in hyporheic water quality revealed by continuous monitoring in a salmon spawning stream

Abstract: Over a 3.5 year period, levels of dissolved oxygen (DO) saturation were continuously monitored in surface waters and at depths of 150 and 300 mm in the hyporheic zone of a riffle in a montane stream where Atlantic salmon spawn. Throughout this period, DO in surface waters remained close to 100% saturation, but exhibited daily variations related to CO 2 cycling driven by diurnal patterns of respiration and photosynthesis. However, in the hyporheic zone, variations were much more dynamic over storm event, season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 45 publications
6
55
0
Order By: Relevance
“…The overall average median contribution from this catchment source to the interstitial sediment-associated organic matter across the three channel sampling sites was 47% (full uncertainty range 0-100%). Increased shear stress in conjunction with higher flows can mobilise inchannel decaying vegetation and evidence has demonstrated that some of this material can infiltrate spawning gravels thereby contributing to oxygen consumption via subsequent decomposition (Whitmore and Clark, 1982;Soulsby et al, 2001Soulsby et al, , 2009. Since much of the instream decaying vegetation will originate from riparian trees and bushes as well emergent and submergent macrophytes, the importance of this source type underscores the linkages between well-connected riparian areas and aquatic ecology in the context of the supply of leaf litter (cf.…”
Section: Basket Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall average median contribution from this catchment source to the interstitial sediment-associated organic matter across the three channel sampling sites was 47% (full uncertainty range 0-100%). Increased shear stress in conjunction with higher flows can mobilise inchannel decaying vegetation and evidence has demonstrated that some of this material can infiltrate spawning gravels thereby contributing to oxygen consumption via subsequent decomposition (Whitmore and Clark, 1982;Soulsby et al, 2001Soulsby et al, , 2009. Since much of the instream decaying vegetation will originate from riparian trees and bushes as well emergent and submergent macrophytes, the importance of this source type underscores the linkages between well-connected riparian areas and aquatic ecology in the context of the supply of leaf litter (cf.…”
Section: Basket Extractionmentioning
confidence: 99%
“…Episodes of low dissolved oxygen supply in the benthos have been attributed to various causes including groundwater upwelling (Malcolm et al, 2003), reduced gravel permeability due to fine sediment ingress (Lisle, 1989;Zimmerman and Lapointe, 2005) which can hamper the removal of toxic metabolic products (Shumway et al, 1964) and enhanced oxygen consumption arising from the infiltration of fine particulate organic matter (Greig et al, 2006;Malcolm et al, 2008;Soulsby et al, 2009;Sear et al, 2013). More specifically, sediment-bound organic matter influences dissolved oxygen supply to incubating progeny in the spawning substrate via two principal mechanisms: direct competition from microorganisms during organic matter decomposition, and; the growth of biofilms which hamper intragravel flow and oxygen availability and may also scavenge potentially toxic substances (House, 2003;Greig et al, 2007;Sader et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in field-based analytical systems are now producing the first long-term, continuous, in situ measurements of some nutrients in water (Jordan et al, 2005;Palmer-Felgate et al, 2008;Soulsby et al, 2009) and enhancing previous studies that measured storm runoff quality in upland and lowland settings (Davies et al, 1992;Evans and Tranter, 1998;Deletic and Maksimovic, 1998). The data generated from in situ studies have been used to demonstrate the benefits of high-frequency sampling in areas such as load estimation accuracy (Rozemeijer et al, 2010;Jordan and Cassidy, 2011;Ferrant et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These processes affect the movement of nutrients and contaminants between groundwater and surface water. The rate at which organic contaminants biodegrade in the HZ can exceed rates in stream water or groundwater away from the stream (Boulton et al 1998;Storey et al 2004;Soulsby et al 2009). The flux dynamic depends considerably on the porosity and permeability of the sediments ; Environment Agency 2009) and can be influenced by clogging.…”
Section: Spring Ecosystemsmentioning
confidence: 99%